Kajian Sosiologi Hukum Terhadap Problematika Bullying dalam Dunia Pendidikan - Erna Susanti (Universitas Bandar Lampung (UBL), 2016)
Sociology of law is a studyof interrelationship between law and society. It is a branch of science to understand, observe, explain by empiric analytical approach regarding law problem confronted with other phenomenon in society. Sociology of law approach show us that the law of state is not the only behavior reference. In reality, the other laws are effectively complied by society.Based on Indonesia constitution, UUD 1945Article 31 Par 3, says the government shall manage and organize national education system to improve priesthood and faith and notable character. In related with bullying, which is a long stand phenomenon have been practically occur in the life of student, the prepetator will constantly intimidate and mocking their friends. It must be stopped due to the reason if the victim will descelerate attending the class. In sociology perspective, any violence is an abuse behaviour. Thus, the ethic enforcement generally coming from self awareness. The situation appear to be very critical to eradicate especially in the realm of education had been conducted systematically out of approaching framework.